Prehistoric beasts - Goldsmith, Andrew (New York Bearport Publishing Co, Inc., 2006)
Which was more powerful - a saber-toothed tiger or a mammoth? One was fast and had very long teeth. The other was huge and had long sharp tusks. However, one was better at surviving on Earth than the other.
Elementary
Keywords: Vertebrates, Fossil; Herbivores, Fossil; Carnivora, Fossil; Dinosaurs